Erratum to “Phytochemicals and Antioxidant Activity of Microalgae Dunaliella salina and Botryococcus braunii” - Ali Ridlo; Delianis Pringgenies; Ribka Anindita Br Perangin-angin; Dafit Ariyanto (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Erratum to “Phytochemicals and Antioxidant Activity of Microalgae Dunaliella salina and Botryococcus braunii” [Jurnal Ilmiah Perikanan dan Kelautan Volume 15 Issue 2, 16 Agustus 2023] Ali Ridlo1* , Delianis Pringgenies1, Ribka Anindita Br Perangin-angin1, and Dafit Ariyanto2 1Department of Marine Sciences, Faculty of Fisheries and Marine Sciences, Universitas Diponegoro, Semarang, Central Java. Indonesia 2Research Center for Oceanography, National Research and Innovation Agency, Jakarta. Indonesia Refers to Phytochemicals and Antioxidant Activity of Microalgae Dunaliella salina and Botryococcus braunii Jurnal Ilmiah Perikanan dan Kelautan Volume 15 Issue 2, 16 Agustus 2023 Ali Ridlo, Delianis Pringgenies, Ribka Anindita Br Perangin-angin, and Dafit Ariyanto https://doi.org/10.20473/jipk.v15i2.36740 In the originally published version of this article, the formula contains a formatting error, and Figure 3 mention wrong solvent names : N heksana, etil asetat, metanol. The authors regret this error and hereby provide the corrected version of the formula and Figure 3. This correction does not affect the scientific content, interpretation, or conclusions of the article. The revised formula is presented below:                             (A-B) % inhibition= -------------  ×100%                                 B The revised Figure 3 mentioned below: The authors would like to apologize for any confusion this may have caused.